THE STATUS OF BUSINESS EDUCATION IN PROMOTING RELIABLE AND SOUND ECONOMIC GROWTH IN THE OIL SECTOR IN DELTA STATE - Oguejiofor, Chinwe Sussan.; Ugonwa F. , Umeh, (IJRDO - Journal of Business Management, 2019)
The status of business education in promoting reliable and sound economic growth in the oil sector in Delta State is the focus of this study. The study adopted a descriptive survey research design and simple random sampling techniques was used to select 80 respondents from 290 staff. The instrument used for data collection was a structured questionnaire. The data collected was presented and analyzed using statistical mean scores while the null hypotheses were tested using t-test statistics at 0.05 level of significance It was revealed that business education creates employment opportunities that contributes to sustainable economic growth. It was also revealed that business education have enormous economic potential and benefit that can lead to economic growth. Based on the findings and the implications of the study, conclusions was drawn and recommendations were made. It was recommended that experts in business education should be immediately drafted into the curriculum review to ensure that the contents to be recommended and taught are in tandem to what is obtainable in the modern day organization practices to deliver national transformation assurances. There should be adequate funding for Business education and that teaching of business education should be left exclusively to the business educators only.